PERSONALITY APPLICATION ACCEPTANCE TEST OF NEW ON PT CANDIDATES USING MULTIMEDIA VISUAL TRIKOMSEL BASIC.NET - Widya Tryantari; Syahril, SKom Syahril, SKom (Jurnal Sistem Informasi, 2006)
With the rapidly growing economy is now also expanding job opportunities that people need to be able to meet the needs of everyday life. So many people who need jobs, so selective in accepting the company is also a human resources (HR) quality. To be able to get a ready to use human resources in the world of work requires a way of selecting an effective and efficient but with significant results. By making this application the authors try to help HR staff to be able to simplify the job of doing one part of the stage personality test is a computerized personality test by using the Visual Basic.Net programming language object-oriented in order to be able to utilize existing facilities therein.